Does Customer Satisfaction Mediate Experiential Marketing and Promotion Against Customer Loyalty at Kentucky Fried Chicken (KFC) Restaurants in City "P" East Java? - Hermanto Hermanto; Ngatimun Ngatimun (International Journal of Social Science and Business, 2023)
This study predicts the influence of Experiential Marketing and promotions on customer loyalty, with customer satisfaction acting as a mediator, within the context of the Kentucky Fried Chicken (KFC) fast-food restaurant in City "P," East Java. The research method employed is quantitative associative. The research sample consists of 100 respondents who are consumers visiting KFC to purchase and enjoy its products. The sampling technique utilized is convenient sampling. Data is analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) analytical tool. Prior to hypothesis testing, an evaluation of the indicators with respect to their constructs (Measurement model) and an assessment of the relationships among variable constructs (Structural model) were conducted, resulting in satisfactory criteria and justifying the continuation of hypothesis testing. The findings demonstrate that Experiential Marketing directly influences customer satisfaction and loyalty, while promotions also directly impact customer satisfaction and loyalty. Furthermore, customer satisfaction, in addition to its direct influence on loyalty, also serves as a complementary mediator between Experiential Marketing and promotions in affecting customer loyalty.